196k views
5 votes
Use the double intercept approach to find the graph of –1 = –y + x

Use the double intercept approach to find the graph of –1 = –y + x-example-1
Use the double intercept approach to find the graph of –1 = –y + x-example-1
Use the double intercept approach to find the graph of –1 = –y + x-example-2
User LotAbout
by
8.0k points

2 Answers

5 votes
We can eliminate A and C
I would say the answer is D
Use the double intercept approach to find the graph of –1 = –y + x-example-1
User Bjornl
by
7.3k points
1 vote

Answer:

option: D

Explanation:

The double intercept form of a line
ax+by=c is given by :


(x)/(A)+(y)/(B)=1.

where A is x-intercept of a graph and B is y-intercept of a graph.

we are here given a equation of a line as:
x-y=-1

which could also be written in a double intercept form as:


(x)/(-1)+(y)/(1)=1

now the graph of the double intercept form passes through points (A,0) and (0,B).

so, the graph here passes through (-1,0) and (0,1).

Hence option D is correct.


User Thibaud Colas
by
7.0k points